2004
DOI: 10.1007/s00467-004-1656-0
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous treatment of transplant renal artery stenosis in children

Abstract: Percutaneous treatment of renal artery stenosis (RAS) is an accepted procedure and numerous reports have been published. However, experience with its use in RAS in the transplanted kidney in children is scarce. Since 1994 we have diagnosed RAS in seven children with the use of Doppler ultrasonography (US), confirming it with percutaneous angiography (PAG). In six of the seven patients percutaneous transluminal angioplasty (PTA) was performed. In one patient a metallic stent was placed due to the extension of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(39 reference statements)
2
6
0
Order By: Relevance
“…In the available literature, we did not fi nd published experiences with CoCr stent implantation in cases of RAS in children. In general, experiences with stent implantation in RAS in children are currently rare with only a few small series been published on children with resistant stenoses due to neurofi bromatosis, Takayasu arteritis and kidney transplant stenoses [5,17,20] . Published data on the long-term follow-up after stent implantation in childhood RAS is rare.…”
Section: Discussionmentioning
confidence: 99%
“…In the available literature, we did not fi nd published experiences with CoCr stent implantation in cases of RAS in children. In general, experiences with stent implantation in RAS in children are currently rare with only a few small series been published on children with resistant stenoses due to neurofi bromatosis, Takayasu arteritis and kidney transplant stenoses [5,17,20] . Published data on the long-term follow-up after stent implantation in childhood RAS is rare.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reported cases of renovascular hypertension, many of which are treated by radiological intervention such as PTA or embolization [11,12,13,14]. But when stenosis is not on the main trunk but on a branch of it, such an intervention is technically difficult.…”
Section: Discussionmentioning
confidence: 98%
“…Renal artery stenosis (RAS) has been reported to occur in 1.5-8.4% of adult transplant recipients (Sankari et al 1996;Wong et al 1996;Jindal et al 2001) and 3.2-8.7% of pediatric renal transplant recipients (McMullin et al 1992; Repetto et al 2004;Ghirardo et al 2014). RAS may occur in the early postoperative period; however, it is usually found to be a late complication.…”
Section: Pediatric Renal Transplantation Complications Arterial Complmentioning
confidence: 99%
“…Treatment of posttransplant RAS with percutaneous transluminal angioplasty (PTA) has been reported to be successful in 82% of adult patients (Jindal et al 2001). As such, PTA has gained acceptance as first-line treatment in adults with RAS, and its use has gained increasing acceptance for pediatric patients (McTaggart et al 2000;Booth et al 2002;Repetto et al 2004;Tullus et al 2008;Corbetta et al 2011;Donaldson 2014). A 2014 study of pediatric transplant recipients found to have RAS reported a success rate of 80% after PTA with significant improvement in graft function (Ghirardo et al 2014).…”
Section: Pediatric Renal Transplantation Complications Arterial Complmentioning
confidence: 99%